Informal markets in sexual and reproductive health services and commodities in rural and urban Bangladesh - Standing, Hilary; Rashid, Sabina; Akram, Owasim (© 2012 Taylor and Francis, 2017)
This book chapter was published in the Transforming Health Markets in Asia and Africa: Improving Quality and Access for the Poor [© 2012 Taylor and Francis] and the definite version is available at: http://www.tandfebooks.com/doi/10.4324/9780203102060